KAJIAN PSIKOLINGUISTIK TERHADAP GANGGUAN MEKANISME BERBICARA (STUDI KASUS RAISYA DAN ATHAYA) - Janella, Tiara; Muzzamil, Ahmad Rabiul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the forms of receptive and expressive (productive) disorders on theÂ lisp children, Raisya and Athaya. This is also to describe a descriptive text and lesson plan model discussing vocabulary as the research implication on the Indonesian language instructionÂ for the 1st-grade of elementary school students in semester 2, 2013 curriculum. This is a case study using a descriptive qualitative approach. The data in the research was collected through Simak Libat Cakap, Pancing, Cakap Semuka, recording, and note-taking techniques. The data analysis methods used were referential pairing and articulatory phonetic pairing. The analysis was presented using formal and informal methods. Based on the analysis, Raisya and Athaya suffered the receptive language disorder in the form of sensory perception (symbol identification) and visual (pictures), whereas the auditory is normal. Afterward, expressive disorder suffered was in the phonetic area. While vocal and diphthong are in the normal state, consonants are the area that often encounters replacement and removal. Meanwhile, the sound additions and inconsistencies were not found in their utterances. Keywords: Language Disorder, Psycholinguistics, Phonology.